Effect of the Addition of 4 wt% Zr to BCC Solid Solution Ti52V12Cr36 at Melting/Milling on Hydrogen Sorption Properties - Kamble, Amol; Sharma, Pratibha; Huot, Jacques (Frontiers in Materials, 2022)
The addition of 4 wt% Zr to Ti52V12Cr36 alloy was carried out in two different ways: arc-melting or ball-milling. The cast alloy showed rapid hydrogen absorption up to 3.6 wt% of hydrogen capacity within 15 min. Ball milling this sample worsened the kinetics, and no hydrogen absorption was registered when milling was carried out for 30 or 60 min. When zirconium is added by ball-milling, the kinetic is slower than that when addition is by arc-melting. This is due to the fact that when added by milling, zirconium does not form a ternary phase with Ti, V, and Cr but instead is just dispersed on the particles’ surface.